2020
DOI: 10.1002/cam4.3623
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following laparoscopic‐assisted resection or open resection for rectal cancer: Findings from AlaCaRT—Australasian Laparoscopic Cancer of the Rectum Trial

Abstract: Background Maintaining employment for adults with cancer is important, however, little is known about the impact of surgery for rectal cancer on an individual's capacity to return to work (RTW). This study aimed to determine the impact of laparoscopic vs. open resection on RTW at 12 months. Methods Analyses were undertaken among participants randomized in the Australian Laparoscopic Cancer of the Rectum Trial (ALaCaRT), with work status available at baseline (presurgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Previous studies reported an RTW time of 2.2 to 9.1 months, and the proportion of employed patients after surgery was 49% to 89%. 12–19 This is partial because most patients in this study were treated using minimally invasive surgery, which was reported to facilitate RTW. 18 In addition, in Japan, there is no public social support system ensuring absence owing to sickness for employees who are unable to work, although almost all large Japanese companies have their own sickness insurance system for their employees.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported an RTW time of 2.2 to 9.1 months, and the proportion of employed patients after surgery was 49% to 89%. 12–19 This is partial because most patients in this study were treated using minimally invasive surgery, which was reported to facilitate RTW. 18 In addition, in Japan, there is no public social support system ensuring absence owing to sickness for employees who are unable to work, although almost all large Japanese companies have their own sickness insurance system for their employees.…”
Section: Discussionmentioning
confidence: 99%
“…12–19 This is partial because most patients in this study were treated using minimally invasive surgery, which was reported to facilitate RTW. 18 In addition, in Japan, there is no public social support system ensuring absence owing to sickness for employees who are unable to work, although almost all large Japanese companies have their own sickness insurance system for their employees. 19 Thus, Japanese patients may be more motivated to RTW than in other countries, such as the United Kingdom and the Netherlands, where state-funded welfare is available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations